In vitro wound healing of tumor cells: inhibition of cell migration by selected cytotoxic alkaloids - Xiaojuan Wang; Charlotte Caroline Decker; Laura Zechner; Sonja Krstin; Michael Wink (BMC, 2019)
Abstract Background Cell migration is involved in several pathological processes such as tumor invasion, neoangiogenesis and metastasis. Microtubules are needed in directional migration. Methods To investigate the effects of microtubule-binding agents (paclitaxel, vinblastine, colchicine, podophyllotoxin), benzophenanthridine alkaloids (sanguinarine, chelerythrine, chelidonine) and other anti-tumor drugs (homoharringtonine, doxorubicin) on cell migration, we performed the in vitro wound healing assay. The interactions between selected alkaloids and microtubules were studied via U2OS cells expressing microtubule-GFP markers. Results The microtubule-binding natural products paclitaxel, vinblastine, colchicine and podophyllotoxin significantly altered microtubule dynamics in living cells and inhibited cell migration at concentrations below apparent cytotoxicity. The benzophenanthridine alkaloid sanguinarine, chelerythrine and chelidonine which affected microtubules in living cells, did not inhibit cell migration. Homoharringtonine (protein biosynthesis inhibitor) and doxorubicin significantly inhibited cell migration, however, they did not exert obvious effects on microtubules. Conclusion In this study, we demonstrated that microtubule-binding agents are effective anti-migrating agents; moreover, homoharringtonine and doxorubicin can be referred as anti-migrating agents, but direct microtubule dynamics are not involved in their mode of action. Our study provides evidence that some alkaloids and other microtubule-binding natural products may be interesting candidates for the development of novel agents against metastasis.